Real-Time Imaging of Gap Progress during and after Composite Polymerization. (August 2017) - Hayashi, J.; Shimada, Y.; Tagami, J.; Sumi, Y.; Sadr, A.
The aims of this study were to observe the behavior of composite and formation of gaps during and immediately after light polymerization using swept source optical coherence tomography (OCT) and to compare the interfacial integrity of adhesives in cavities through 3-dimensional (3D) image analysis. Forty tapered cylindrical cavities (4-mm diameter, 2-mm depth) were prepared in bovine incisors and restored using Bond Force (BF), Scotchbond Universal Adhesive (SBU), OptiBond XTR (XTR), or Clearfil SE Bond 2 (SE2), followed by Estelite Flow Quick flowable composite. Real-time imaging was performed at the center of restoration by the OCT system (laser center wavelength: 1, 330 nm; frequency: 30 KHz) during and up to 10 min after light curing. The 3D scanning was performed 0, 1, 3, 5, and 10 min after light curing. The percentages of sealed enamel and dentin interface area (E%, D%) were calculated using Amira software. In real-time videos, the initial gaps appeared as a bright scattered area mainly on dentin floor and rapidly progressed along the cavity floor. The timing, rate, and extent of gap formation were different among the specimens. From 3D visualization, gap progress could be seen on both enamel and dentin even after irradiation; furthermore, typical toroidal gap patterns appeared at the dentin floor of BF and SBU. XTR and SE2 showed nearly perfect sealing performance on the dentin floor up to the 10 min that images were recorded. From quantitative analysis, SE2 and XTR showed significantly higher E% and D% than other groups. SBU showed the smallest E% and BF showed a significantly smaller D% than other groups ( P < 0.05). In conclusion, real-time observation of composite placement and 3D quantification of interfacial gaps were implemented within the experimental limitations. Interfacial gap formation during polymerization of the composite depended on the adhesive system used. The formed gaps continued to propagate after composite light curing finished.